2022
DOI: 10.3390/ma15031240
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Carbonation Durability of Kaolin Strengthened with Slag Portland Cement

Abstract: Slag Portland cement is an environmentally friendly and energy-saving product, which is widely used in cement-reinforced soil. This study used slag Portland cement-reinforced soil as the research object and P.O 42.5 + kaolin (POK) as the reference group. The carbonation depth and strength of P.S.A 42.5 + kaolin (PSK) at different curing times were analyzed using carbonation depth, uniaxial ground pressure strength, scanning electron microscopy (SEM), energy-dispersive spectroscopy (EDS) and X-ray diffraction (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
0
0
1
Order By: Relevance
“…Picos de carbonato de cálcio ocorreram em 2θ = 29,1° e 47, 1°. A presença da fase carbonato de cálcio pode ser devido à carbonização durante o experimento pelo CO 2 atmosférico e hidróxido de cálcio [81,82]. Além disso, LIANG et al [83] relata que a concentração de quitosana tem forte influência nas morfologias do CaCO 3 .…”
Section: Análises Microestruturalunclassified
“…Picos de carbonato de cálcio ocorreram em 2θ = 29,1° e 47, 1°. A presença da fase carbonato de cálcio pode ser devido à carbonização durante o experimento pelo CO 2 atmosférico e hidróxido de cálcio [81,82]. Além disso, LIANG et al [83] relata que a concentração de quitosana tem forte influência nas morfologias do CaCO 3 .…”
Section: Análises Microestruturalunclassified
“…However, excessive amounts of gypsum can lead to the production of excessive amounts of AFt [59], resulting in volume expansion and the breaking of hardened paste. Previous studies have shown that the optimal proportion of gypsum in slag-based geopolymer is between 6% and 10% [60]. Additionally, the reactivity of slag powder increases significantly when the concentration of gypsum and quicklime is within the range of 5-10% and 10-20%, respectively [61].…”
Section: Strength Of Mortarmentioning
confidence: 99%